2014
DOI: 10.1093/europace/euu233
|View full text |Cite
|
Sign up to set email alerts
|

Current use of implantable electrical devices in Sweden: data from the Swedish pacemaker and implantable cardioverter-defibrillator registry

Abstract: Pacemaker and ICD implantation rates seem to have reached a level phase in Sweden. Implantable cardioverter-defibrillator and CRT implantation rates are very low and do not reflect guideline indications. Gender differences in CRT and ICD implantations are pronounced. Device and patient survival rates are variable, and should be considered when deciding device type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
4
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 31 publications
4
48
4
4
Order By: Relevance
“…Electrocardiographical indications for PM were related to AV conduction disorders and AF in 38% and 15%, respectively 37. Another study demonstrated that first-degree AV block was associated with a threefold increased risk of future PM and also with an increased risk of AF 38.…”
Section: Discussionmentioning
confidence: 99%
“…Electrocardiographical indications for PM were related to AV conduction disorders and AF in 38% and 15%, respectively 37. Another study demonstrated that first-degree AV block was associated with a threefold increased risk of future PM and also with an increased risk of AF 38.…”
Section: Discussionmentioning
confidence: 99%
“…A large multinational comparison of CRT‐D and CRT‐P implant rates reveal that among the 10 countries with the highest per capita rates of CRT implantation, CRT‐P devices range from 17% (Italy) to 49% (Hungary) of CRT devices 30. In the Swedish heart failure registry,31 63% of patients receiving CRT were implanted with CRT‐P 32. Our data accord with a smaller, single‐center study from the Cleveland Clinic, which demonstrated that among Class III/IV heart failure patients receiving CRT, 95% received CRT‐D versus CRT‐P 33.…”
Section: Discussionmentioning
confidence: 99%
“…For example, higher rates of cardiac resynchronization therapy (CRT)-pacing versus CRT-Defibrillator were seen in the Swedish registry. 11 The authors felt this was at least in part because key leaders thought CRT-P was as effective in reducing mortality, and lower in cost and complication rate compared to CRT-D. 12 It is also possible that differences in healthcare reimbursement systems may impact the choice to implant or refer for an ICD. Finally, there may also be cultural differences in patient preference, whereby patients may view the risks and benefits of ICD therapy differently in different countries.…”
Section: Paulvarosy@vagov or Paulvarosy@ucdenveredumentioning
confidence: 99%